Discrete quadratic splines - Surendra Singh Rana (International Journal of Mathematics and Mathematical Sciences)
In the present paper, we define a new class of discrete splines and study the existence, uniqueness, and convergence properties of discrete quadratic splines satisfying the Mean Averaging Condition.